Conditions for the existence of peaks in the Sigma hypernucleus spectra - Petridou, Th.; Daskaloyannis, C. (HNPS Advances in Nuclear Physics, 2020)
The (K-, π±) sigma hypernuclear spectrum is studied qualitatively in the Green function approach, using a solvable interaction model. The general features of the spectrum are explained. The necessary conditions for the existence of peaks in the spectrum are also studied. We show that the resonant peaks can be distinguished in the case of a real strong spin-orbit potential with a relatively weak Sigma to Lambda conversion.